An Evaluation Framework For Resort Operators In Eco-Tourism Industry In Malaysia: Towards A Synthesis. - Abdullah, Shardy; Yusof, Nor'Aini; Salleh, llias S.; Abd Razak, Arman; Mohd Shafiei, Mohd Wira (2008)

(untitled)
There is increasing competition in eco-tourism destination and Malaysia has the opportunity to benefit from this industry. Little is known about tourists' needs and expectations to the eco tourism destinations albeit the overwhelming attention given. Therefore, this issue is subjected for further scrutiny. In the same vein, organizational culture has been regarded as one of the biggest challenges in the management in service industries.